1982
DOI: 10.1002/1097-0142(19820315)49:6<1316::aid-cncr2820490640>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Results in patients with breast cancer treated by radical mastectomy and postoperative irradiation with no adjuvant chemotherapy

Abstract: In 1963 an electron beam became available, making irradiation of the chest wall technically easy. In addition to peripheral lymphatic irradiation in patients with positive axillary nodes and/or the tumor in the inner quadrants or centrally located, patients with tumor larger than 5 cm or with grave signs and/or a significant incidence of positive axillary nodes received chest wall irradiation. None of the patients has received elective chemotherapy. Disease-free survival rates at ten years are 54% for the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…In fact, early randomized trials of breast cancer with PMRT did not prove the improvement in overall survival and just demonstrated that the risk of locoregional recurrence was reduced [810]. With the popularity of systemic therapy and the development of radiotherapy, several studies have demonstrated that the patients of breast cancer may benefit from the administration of PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, early randomized trials of breast cancer with PMRT did not prove the improvement in overall survival and just demonstrated that the risk of locoregional recurrence was reduced [810]. With the popularity of systemic therapy and the development of radiotherapy, several studies have demonstrated that the patients of breast cancer may benefit from the administration of PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее ранние данные о роли ЛТ после мастэктомии относятся к исследованиям, в которых больные были про-лечены без системной терапии и с применением старой радиотерапевтической техники [1,2]. Авторы в них проде-монстрировали улучшенные показатели локорегионального контроля, но никаких преимуществ в общей выживаемости.…”
Section: ключевые слова: лучевая терапия радикальная мастэктомия неunclassified
“…Early randomized trials of postmastectomy radiation generally demonstrated a reduction in the risk of locoregional recurrence of breast cancer without improvement in overall survival, particularly before the advent of effective systemic therapies. [103][104][105][106] As experience with systemic therapy for breast cancer grew, it became increasingly apparent that certain subgroups of patients might harbor a burden of residual locoregional disease that systemic therapies could not eradicate and, thus, might benefit from the administration of postmastectomy radiation therapy. Therefore, several trials were initiated to explore the role of postmastectomy radiation in conjunction with chemotherapy.…”
Section: Postmastectomy Radiotherapymentioning
confidence: 99%